Intraoperative Real-Time Near-Infrared Image-Guided Surgery to Identify Intracranial Meningiomas via Microscope - Muto, Jun; Mine, Yutaka; Nishiyama, Yuya; Murayama, Kazuhiro; Yamada, Seiji; Kojima, Daijiro; Hayakawa, Motoharu; Adachi, Kazuhide; Hasegawa, Mitsuhiro; Lee, John Y. K.; Hirose, Yuichi (Frontiers in Neuroscience, 2022)
Meningiomas are a common pathology in the central nervous system requiring complete surgical resection. However, in cases of recurrence and post-irradiation, accurate identification of tumor remnants and a dural tail under bright light remains challenging. We aimed to perform real-time intraoperative visualization of the meningioma and dural tail using a delayed-window indocyanine green (ICG) technique with microscopy. Fifteen patients with intracranial meningioma received 0.5 mg/kg ICG a few hours before observation during the surgery. We used near-infrared (NIR) fluorescence to identify the tumor location. NIR fluorescence could visualize meningiomas in 12 out of 15 cases. Near-infrared visualization during the surgery ranged from 1 to 4 h after the administration of ICG. The mean signal-to-background ratio (SBR) of the intracranial meningioma in delayed-window ICG (DWIG) was 3.3 ± 2.6. The ratio of gadolinium-enhanced T1 tumor signal to the brain (T1BR) (2.5 ± 0.9) was significantly correlated with the tumor SBR (p = 0.016). Ktrans, indicating blood–brain barrier permeability, was significantly correlated with tumor SBR (p < 0.0001) and T1BR (p = 0.013) on dynamic contrast-enhanced magnetic resonance imaging (MRI). DWIG demonstrated a sensitivity of 94%, specificity of 38%, positive predictive value (PPV) of 76%, and negative predictive value (NPV) of 75% for meningiomas. This is the first pilot study in which DWIG fluorescence-guided surgery was used to visualize meningioma and dural tail intraoperatively with microscopy. DWIG is comparable with second-window ICG in terms of mean SBR. Gadolinium-enhanced T1 tumor signal may predict NIR fluorescence of the intracranial meningioma. Blood–brain barrier permeability as shown by Ktrans on dynamic contrast-enhanced MRI can contribute to gadolinium enhancement on MRI and to ICG retention and tumor fluorescence by NIR.